Electrical and thermal properties of PLA/CNT composite films - Ceregatti,Thayara (2017)
ABSTRACT Conducting polymers presents many potential applications such as biosensors and biofuelcells. However, to be used in those devices, a thin film must be deposited onto a conducting and biocompatible substrate. In this work, carbon nanotubes (CNT) were mixed in a poly (lactic acid) - PLA - matrix with different compositions (from 0.25 to 5.0 %) in order to form conducting composites suitable to the deposition of a conducting polymer. Thermal properties of PLA/CNT composites were evaluated by Thermogravimetry (TG) and Differenctial Scanning Calorimetry (DSC), and the electrical properties were evaluated by 2-probe method and by Electrochemical Impedance Spectroscopy (EIS). Thermal analysis showed and influence of CNT quantities on PLA crystallization, which also showed an influence on conductivity of the tested materials. Besides, the conductivity of PLA/NTC 1% film showed similar values of the conducting polymer (Pani) itself.